Adaptive strategies of Parian Chinese fictive kinship and credit in seventeenth-century Manila - Kueh, Joshua (2013)
Based on a seventeenth-century baptismal book of the Parián, a 1689 list of debts owed to non-Catholic Chinese, and a 1690 membership list for gremios de sangleyes infieles, this article argues that adaptation by the Chinese in Manila to secure themselves and their livelihoods followed two major strategies: (a) fictive kinship in the form of compadrazgo (coparenthood) and padrinazgo (godparenthood), and (b) extending credit. The Chinese used both strategies to create or solidify networks of mutual obligation and aid within their own community and with other residents of Manila. These strategies helped spin webs of interconnection that made colonial society stable and viable.
Keywords: Chinese -- Manila City -- Social life and customs; Kinship; Sponsors (Godparents); Credit; Chinese -- Philippines -- History